(untitled) (Research, Society and Development, 2022)
The present study aimed to know the scientific evidence on the relationship of increased risk of bone fracture with the use of proton pump inhibitors (IBP’s) in patients with pre-existing comorbidities. A literature review of scientific articles published on the PubMed platform was carried out, including all original articles in the last five years, according to the pre-established inclusion criteria. It was observed that the risk of bone fracture is associated with the time of use of IBPs in patients with different age groups, with or without comorbidities, among which we can mention osteoporosis and diabetes as the most prevalent. It was also evidenced that patients on hemodialysis or those with liver cirrhosis are at increased risk for bone fractures. Continuing, it was possible to verify that the use of these drugs in gastroesophageal reflux disease in pregnant women does not affect the fetal bones to a clinically significant extent. The results of this review allow us to suggest that caution should be exercised in prescribing this class of drug, in addition to monitoring this adverse event regarding its use depending on the target population, and caution should be exercised in prescribing the dose and duration of treatment. Therefore, attention is drawn to the appearance of fractures, especially in view of how this impairs the quality of life of patients who need to undergo anti-ulcer therapy for a long time.